2021
DOI: 10.3390/educsci11100631
|View full text |Cite
|
Sign up to set email alerts
|

Telework Experience of Pedagogues during the COVID-19 Pandemic: Strong Learning Seniors and Relaxed Leaders?

Abstract: Due to the wide application of remote teaching during the COVID-19 pandemic, the foundations of the education system have been shaken; education has entered a new era of teaching and learning on digitalized platforms. How do pedagogues evaluate their experiences when information technologies have become the main axis of carrying out their work? What impact did telework have on pedagogues as employees of an education institution or as individuals? What could be expected from older pedagogues in the shift to usi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 32 publications
0
2
0
1
Order By: Relevance
“…The Czech Republic ranked among countries with less than 5% of the workforce working from home (ILO, 2020, p. 3). The topic of telework caught the attention of a wide range of scientists approaching it from many angles (Raišienė et al, 2021). Studies revealed differences in the usage of homeworking across countries (Beňo, 2021;Frantíková et al, 2017;Prosser, 2017) and even the impact of various forms of on-distance work on sustainability (Vaishar & Šťastná, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…The Czech Republic ranked among countries with less than 5% of the workforce working from home (ILO, 2020, p. 3). The topic of telework caught the attention of a wide range of scientists approaching it from many angles (Raišienė et al, 2021). Studies revealed differences in the usage of homeworking across countries (Beňo, 2021;Frantíková et al, 2017;Prosser, 2017) and even the impact of various forms of on-distance work on sustainability (Vaishar & Šťastná, 2019).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Earlier surveys on teleworking, carried out at different times and in different samples in Lithuania during the pandemic, have shown specific results on teleworkers compared to other Western countries. For instance, teleworking is less valued by men and younger people, as well as by some professional communities (Raišienė et al, 2020;Raišienė et al, 2021). On the other hand, Tvaronavičienė et al (2021) prove that youth highly appreciate possibilities for education and positive family relationships maintaining in their system of well-being factors, which, in their turn, are more available in the case of teleworking.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Para Baranov et al (2022) en los últimos años, el avance de la tecnología digital ha permitido aumentar la velocidad y procesamiento de la información con la consecuente producción de nuevos retos y desafíos; esto, sumado a la reciente situación mundial de pandemia del COVID-19, ha ocasionado según Raišienė et al (2021) que los países vieran afectados sus planteles educativos de todos los niveles, así en el año 2020 la mayoría de ellos, tuvo que cerrar las instalaciones escolares afectando al 91% de los estudiantes a nivel mundial dejando sin servicio educativo aproximadamente 1600 millones, de los cuales, 101 millones de niños y jóvenes se vieron agraviados en el logro de las competencias de escritura y lectura, entre otras competencias; en este contexto, es importante señalar que 255 millones de empleos a tiempo completo se perdieron, esto, incidió en el poder adquisitivo de las familias y se les dificultó la adquisición de equipos tecnológicos para encarar con éxito los modelos educativos sustentados en las (TIC) Tecnologías de Información y Comunicación (UN, 2022; UNESCO, 2019).…”
Section: Introductionunclassified